On the Anormal Uniqueness for a Class of First Order Coupled Elliptic System (Journal of Partial Differential Equations, 2020)
In this paper, we studied and completely solved the problem on the anornal uniqueness of the equation system {u_x + ixu_y = -ix&sup2&#934v_y v_z + ixu_y = -ix&sup2&#934v_y The so-called anormal uniqueness means as follows: suppose all order derivatives of u vanish on &#8706D, one can draw the conclusions of u = 0(D), v &#8801 const(D).
Keywords: Coupled elliptic system; Anormal uniqueness